In Brief: Picturing the complex world of chromatin remodelling families. Issue 4 (19th August 2015) - Witkowski, Leora; Foulkes, William D
Abstract: Over the past decade, chromatin remodelling emerged as one of the most important causes of both abnormal development and cancer. Although much has been written about one or another of the complexes, no recent concise summary of the chromatin remodelling families as a whole is available. In this short review, we introduce the family members, briefly summarize their role in developmental abnormalities and neoplasia, and outline the different ways in which these families remodel chromatin. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.